CDKN2A Mutation: A Patient’s and Physician’s Experience - Yaelle Shaked; Alyssa Swearingen; Tracey N. Liebman (Dermatology and Therapy)
Abstract This article discusses both the patient’s and physician’s perspective on the CDKN2A mutation. After an intriguing interview with the patient, the author writes about the patient’s feelings, thoughts, and overall experience when he was diagnosed with the CDKN2A mutation. The patient’s story discusses what prompted the patient to get tested for the mutation and how the diagnosis later impacted his life and that of his family. The author describes the clinical relevance of the CDKN2A mutation and the current guidelines for testing. The author highlights the need to recognize patients with familial melanomas as high risk and educate the patient on the importance of routine dermatological surveillance.